PENGARUH PENANAMAN MODAL ASING DAN TINGKAT DAYA SAING TERHADAP EKSPOR INDUSTRI MANUFAKTUR INDONESIA - Soeharjoto Soeharjoto (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2016)
Export manufacturing industry contributes to economic growth in Indonesia. The supporting element of the export manufacturing industry is Foreign Direct Investment (FDI) and competitiveness. The purpose of this study is to prove whether foreign investment and the level of competitiveness as measured by Index of Revealed Comparative Advantage (RCA) affect the performance of Indonesia's manufacturing industry exports. As for the results of this research are using a multiple regression approach was FDI and RCA had a positive and significant effect against the export manufacturing industry in Indonesia.